Dress, Appearance, and Diversity in U.S. Society - Reddy-Best, Kelly L. (Open textbook library., 2020)
This book introduces topics about identity, dress, and the body. Through the content, readers explore how individuals and communities use dress as a way to communicate (i.e. “negotiate” in fashion studies) their various identities. There is heightened attention to social justice, power, privilege, and oppression. That is, the content focuses on the experiences of historically marginalized communities and the ways they navigate dress and dressing their bodies in different contexts. In the first part of the book, readers are introduced to concepts and theories related to fashion, clothing, dress, and/or accessories. In the second part, readers examine the role that fashion, clothing, dress, and/or accessories play in identity development for individuals in marginalized communities in the United States.